Optimizing Learning Quality Through Program Planning and Evaluation in Islamic Educational Institutions - Inayah Alfiyani; Rusdiana Navlia (Penerbit Hellow Pustaka, 2025)
Islamic education is the name of a system, namely the Islamic education system. Islamic Religious Education, here, refers to the care and guidance of students so that after completing their education, they can understand and practice Islamic teachings and make them a way of life. The method used in this article is library research, namely research that utilizes written materials such as manuscripts, books, magazines, newspapers, and other documents. The results of this research, namely optimizing learning quality through program planning and evaluation in educational institutions, are very helpful for the future development of learning quality. With appropriate learning planning, learning objectives in Islamic educational institutions, especially teaching and learning activities, are easily achieved as expected. Furthermore, program evaluation in Islamic education is a crucial instrument in ensuring that Islamic education is not only relevant but also effective in achieving the desired educational goals. The role of the principal in this context cannot be ignored. The principal is not only an administrative leader but also a figure responsible for determining the direction and quality of Islamic education in schools. Thus, the principal's role extends beyond the administrative implementation of evaluations to include developing effective evaluation strategies, facilitating the evaluation process, and integrating evaluation results into daily educational policies and practices. Islamic education program evaluations also take various forms, ranging from curriculum evaluation and teaching methods to student achievement assessments.